Recurrent SLC1A2 variants cause epilepsy via a dominant negative mechanism. Issue 6 (26th April 2019) - Stergachis, Andrew B.; Pujol‐Giménez, Jonai; Gyimesi, Gergely; Fuster, Daniel; Albano, Giusppe; Troxler, Marina; Picker, Jonathan; Rosenberg, Paul A.; Bergin, Ann; Peters, Jurriaan; El Achkar, Christelle Moufawad; Harini, Chellamani; et al.
Abstract : SLC1A2 is a trimeric transporter essential for clearing glutamate from neuronal synapses. Recurrent de novo SLC1A2 missense variants cause a severe, early onset developmental and epileptic encephalopathy via an unclear mechanism. We demonstrate that all 3 variants implicated in this condition localize to the trimerization domain of SLC1A2, and that the Leu85Pro variant acts via a dominant negative mechanism to reduce, but not eliminate, wild‐type SLC1A2 protein localization and function. Finally, we demonstrate that treatment of a 20‐month‐old SLC1A2 ‐related epilepsy patient with the SLC1A2‐modulating agent ceftriaxone did not result in a significant change in daily spasm count. ANN NEUROL 2019;85:921–926.